1-Nitropyrene induces acute lung injury via SYVN1/Caspase-11-mediated apoptosis and pyroptosis in pulmonary epithelial cells - Ding, Zhao-Lei; Ma, Yi-Chen; Liu, Chuan-Mei; Lu, Xiu; Wang, Rong-Rong; Tang, Min-Min; Hua, Dong-Xu; Zheng, Ling; Zhao, Hui; Fu, Lin (Frontiers in Pharmacology, 2026)
Background1-Nitropyrene (1-NP) is harmful to the respiratory system and can evoke acute lung injury (ALI). Pyroptosis and apoptosis, two important types of programmed cell death, are involved in the pathological process of ALI. However, the roles and mechanisms of pyroptosis and apoptosis on 1-NP-incurred ALI remain unclear.MethodsAll the mice were exposed to a single dose of 1-NP (20 μg/mouse, dissolved in saline) or normal saline via intratracheal instillation. At different times after 1-NP exposure, the mice were sacrificed. Mouse lung epithelial (MLE-12) cells were incubated with 1-NP (5 μM), the indicators of pyroptosis and apoptosis were detected.ResultsPulmonary pathological injury and inflammatory cell infiltration was observed in 1-NP-exposed mice. Additionally, the indicators of apoptosis, Bcl-2 was downregulated, Bad and Caspase-3, and apoptotic cells were increased in 1-NP-exposed mouse lungs and mouse lung epithelial (MLE-12) cells. Meanwhile, the proteins of GSDMD and Pro- and Cleaved Caspase-11 and the mRNAs of Il-1β and Il-18, which are markers of pyroptosis, were increased after 1-NP treatment. Moreover, pretreatment with wedelolactone (WED), an antagonist of Caspase-11, alleviated 1-NP-induced ALI. As expected, pharmacological inhibition or genetic deletion of Caspase-11 abolished 1-NP-induced apoptosis and pyroptosis. Interestingly, 1-NP attenuated Caspase-11 proteasome degradation. Mechanistically, 1-NP downregulated the expression of SYVN1, an E3 ubiquitin ligase of Caspase-11. 1-NP promoted the interaction between SYVN1 and Caspase-11 and inhibited Caspase-11 ubiquitination and subsequent proteasome degradation. Transfection with SYVN1 overexpression plasmids abolished 1-NP-mediated the reduction of Caspase-11 ubiquitination-dependent degradation, apoptosis, and pyroptosis.ConclusionsThese results revealed that acute 1-NP may induce ALI via Caspase-11-mediated apoptosis and pyroptosis by downregulating SYVN1.